2011
DOI: 10.1007/s00520-011-1152-6
|View full text |Cite
|
Sign up to set email alerts
|

Palliative care consultation in pediatric oncology

Abstract: The majority of children in this study who died from cancer were referred to palliative care. Oncologists should strive to refer patients early in their disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
67
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 12 publications
6
67
0
3
Order By: Relevance
“…This percent is lower than other contemporary reports. 7,16,17 Although the completeness and accuracy of the billing codes cannot be verified, all hospitals had patients with the PC V-code, so it is unlikely that the low percent of patients is due to lack of coding for services. If the billing codes were missing in some cases, they are likely to be randomly missing, so the trends found should be representative.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This percent is lower than other contemporary reports. 7,16,17 Although the completeness and accuracy of the billing codes cannot be verified, all hospitals had patients with the PC V-code, so it is unlikely that the low percent of patients is due to lack of coding for services. If the billing codes were missing in some cases, they are likely to be randomly missing, so the trends found should be representative.…”
Section: Resultsmentioning
confidence: 99%
“…18 Previous studies have demonstrated a delay in referral to PC based on the belief that a referral is not needed until curative treatment is no longer the sole goal. 7,19 More recently PC and curative care are being delivered concurrently; however, further investigation is needed to determine when, in the course of illness, children are referred to PC.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the fact that palliative care is now widely recognized as a critical part of excellent care for children with life-limiting diseases such as cancer, patients continue to receive this care very late in their illness trajectory [12,13]. In 1 study, the median time between palliative care consultation and death was only 8 days [14].…”
Section: Ray Barfieldmentioning
confidence: 94%